Decline in telomere length with increasing age across nonhuman vertebrates: A meta‐analysis. Issue 23 (7th September 2021) - Remot, Florentin; Ronget, Victor; Froy, Hannah; Rey, Benjamin; Gaillard, Jean‐Michel; Nussey, Daniel H.; Lemaitre, Jean‐François
Abstract: The prediction that telomere length (TL) shortens with increasing age is a major element in considering the role of telomeres as a key player in evolution. While telomere attrition is found in humans both in vitro and in vivo, the increasing number of studies reporting diverse age‐specific patterns of TL challenges the hypothesis of a universal decline of TL with increasing age. Here, we performed a meta‐analysis to estimate the relationship between TL and age across 175 estimates encompassing 98 species of vertebrates. We found that, on average, TL does decline with increasing age during adulthood. However, this decline was weak and variable across vertebrate classes, and we also found evidence for a publication bias that might weaken our current evidence of decreasing TL with increasing age. We found no evidence for a faster decline in TL with increasing age when considering the juvenile stage (from birth to age at first reproduction) compared to the adult stage. Heterogeneity in TL ageing rates was explained by the method used to measure telomeres: detectable TL declines with increasing age were found only among studies using TRF with in‐gel hybridisation and qFISH methods, but not in studies using qPCR and Southern blot‐based TRF methods. While we confirmed that TL declines with increasing age in most adult vertebrates, our results identify an influence of telomere measurement methodology, which highlights the need to examine more thoroughly the effect of the method of measurement on TL estimates.